Pengaruh Current Ratio, Debt To Equity Ratio Dan Return On Assets Terhadap Price To Book Value Dengan Divident Payout Ratio Sebagai Variabel Intervening Pada Perusahaan Manufaktur Sub Sektor Farmasi - Syamsinah Sirait; Eka Nurmala Sari; Muis Fauzi Rambe (Jurnal AKMAMI (Akuntansi Manajemen Ekonomi), 2021)
The data used in this research is quantitative data sourced from secondary data. Data analysis techniques in this study are using path analysis, classical assumption test, multiple linear regression, t test, F test and coefficient of determination. The results of this study indicate partially that: (1) The current ratio has a negative effect on the dividend payout ratio. (2) Debt to Equity Ratio has a negative effect on the dividend payout ratio. (3) Return On Assets has a negative effect on the dividend payout ratio. (4) Current Ratio has a positive effect on Price to Book Value. (5) Debt to Equity Ratio has a positive effect on Price to Book Value. (6) Return on Assets has a positive effect on Price to Book Value. (7) Dividend Payout Ratio plays a role in mediating Current Ratio to Price to Book Value. (8) Dividend Payout Ratio plays a role in mediating the Debt to Equity Ratio to Price to Book Value. (9) Dividend Payout Ratio plays a role in mediating Return On Assets to Price to Book Value. (10) Dividend Payout Ratio has a positive effect on Price to Book Value.